Enriching Students’ Vocabulary through Quizlet in Reading Class - Pitriani, Pitriani; Friatin, Lilies Youlia; Irianti, Leni (Universitas Galuh, 2024)
This study explored teaching media “Quizlet” to enrich students’ vocabulary in reading class. This study aimed to analyze the students’ perceptions on the use of Quizlet as teaching media in reading class. This qualitative case study research was conducted in one of an Islamic Senior High School in Ciamis. This study involved a tenth- grade consisted of seventeen students which were chosen purposively as the sample of the study. The data were collected by using questionnaire. The results of this study indicate that students have positive perceptions about using Quizlet as a learning media to enrich their vocabulary. Students agreed that the Quizlet application motivated them to learn English vocabulary and improved their learning performance. It can be concluded that the Quizlet application is considered as a useful and fun learning media to enrich students' vocabulary. Furthermore, the researcher recommends that further researchers investigate the use of Quizlet at various levels of education to get more in- depth and specific results regarding the use of Quizlet media in learning vocabulary.